KUALITAS SPERMATOZOA BABI LANDRACE YANG DIBERI EKSTRAK DAUN KELOR (Moringa oleifera Lam.) SEBAGAI ANTIOKSIDAN PADA SUHU PENYIMPANAN BERBEDA - Marisa Aplugi; Cynthia D Gaina; Nancy D. F. K. Foeh (Jurnal Veteriner Nusantara, 2020)
This study aims to determine the quality of Landrace porkspermatozoa with the addition of natural thinners of lontar fruit juice and Moringa oleifera Lam. Leaf extract as antioxidants stored at different storage temperatures, namely 5°C (freezer),15°C (refrigerator) and 22°C (air-conditioned room). Semen was collected six times and evaluated both macroscopically and microscopically. The best quality of semen was semen with spermatozoa motility> 70%, concentration> 200x106 cells / ml and abnormal spermatozoa <20%. In this study, there were three treatments, in which the cement with antioxidant diluents was stored at 15°C. (treatment I), 22°C (treatment II) and 5 oC (treatment III). The results showed at the 36th hour of storage the temperature was 22°C with a motility of 55.00 ± 0.20% and a viability of 72.50 ± 0.27%, a temperature of 15°C with a motility of 55.00 ± 0.28% and a viability of 64.50 ± 0.20%, and a temperature of 5°C with a motility of 50.00 ± 0.50 % and viability 57.50 ± 0.33%. It was concluded that the water thinner of lontar fruit and the antioxidant of Moringa oleifera Lam. Leaf extract were able to maintain the quality of the liquid Landrace pig semen at different storage temperatures. A significant difference (P≤0.05) occurred between the 5°C and 22°C treatment, while the 15°C temperature was not significantly different (P≥0.05) with the 5°C and 22°C temperatures.